Gestão democrática do ensino público: um paradoxo da democracia liberal burguesa? - o caso do Ceará - Silva, Sonia de Oliveira da (2021)
The research analyzes the possible relationships between the democratic management of public education in the state of Ceará and the paradoxical relationship between the conception of democratic management and the excluding sociopolitical and economic order that marks the Brazilian state and the Ceará context. For the development of the research, the investigation of the municipal public education systems of sixteen municipalities located in the immediate geographic region of Fortaleza was adopted as a cut-off. With regard to theory and method, the research was based on the historical-dialectical materialist perspective. Thus, in relation to the methodology, instruments were used that collaborate in the development of data and information collection, which enabled a theoretical dialogue with the research field in a continuous process of qualitative-quantitative analysis. Thus, legal documents that were instituted from the 1990s and that deal with the management of education were analyzed, namely: the section of the Municipal Organic Law, the law document that provides for the municipal education system and others legal documents that provide for the management of public education in the municipalities that make up the Immediate geographic region of Fortaleza. When discussing the main conceptions of civil society and the State, the formation of the Brazilian State and education along the constituents, it was observed that civil society is part of the State and is permeated by conflicts of interests of social classes belonging to the economic structure. Likewise, it is the sphere that will operate conditions, organize and defend these interests and dispute hegemony and, in this dispute, directly influence the entire process of implementing the democratic management of public education. In the analysis of the collected data, it was also evidenced that in the municipal legislation of the municipalities that make up the region considered in the research, the mention of the principles, spaces and mechanisms of participation are present, even if infrequently. They also point out that, in only a few cases, the set of spaces and mechanisms for participation correspond to the principles of democratic management. Regarding the spaces and mechanisms for participation approved by the law, the Municipal Education Plan and the Municipal Education Council appeared more frequently. Less frequently were spaces and mechanisms: Political-Pedagogical Project; School Board and Election of Directors. It is concluded that although democracy in a context of society and State in the capitalist mode of production seems to be weakened, it still represents a possibility of participation. Thus, the internal conditions of participation, material, institutional, political-social and ideological, not existing, does not mean that there are no actions in favor of participation. Thus, it is understood that democratic management is established in the context of struggles, confrontation and political dispute